Two new and one poorly known species of the Cryptoperla formosana species group (Plecoptera: Peltoperlidae) from China - Mo, Raorao; Liu, Ruijun; Wang, Guoquan; Li, Weihai; Murányi, Dávid (Zootaxa, 2021)
One poorly known and two new species of the Cryptoperla formosana species group from China, C. aculeata (Wu, 1973), C. bicornata sp. nov., and C. cunicidata sp. nov. are presented. Cryptoperla bicornata is the first record of the genus from Henan Province, while C. cunicidata is a new generic and family record for Guangdong Province. A complementary description of C. aculeata is given. Illustrations and color images are provided for each species and each is compared with related congeners of the C. formosana species group. A provisional key to the known species of the group is also presented.